2019
DOI: 10.1021/acs.inorgchem.8b02971
|View full text |Cite
|
Sign up to set email alerts
|

(Spectro)electrochemical and Electrocatalytic Investigation of 1,1′-Dithiolatoferrocene–Hexacarbonyldiiron

Abstract: Hexacarbonyldiiron bridged by a 1,1′dithiolatoferrocene, [Fe(C 5 H 4 S) 2 {Fe(CO) 3 } 2 ] (1), was synthesized, and the electrochemistry showed reversible oxidation at the Fe(C 5 H 4 S) 2 site and quasi-reversible reduction at the hexacarbonyldiiron site. Spectroelectrochemical techniques showed reduction-induced ligand isomerization, where the thiolate ligand went from bridging to terminal and one carbon monoxide ligand moved to a quasi-bridging position; this mechanism was further supported by cyclic voltamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…The EPR signal is a triplet with a 1:2:1 intensity ratio ascribed to two equivalent 31 P nuclei with a( 31 P) of 13.3 G. The time/potential profile of the EPR intensity allows its assignment to the first reduction step. The EPR parameters of the radical anion are very similar to those of a series of [Fe 3 (CO) 9 (PR) 2 ] − radical anions produced by chemical reduction of the corresponding Fe 3 (CO) 9 (PR) 2 clusters by cobaltocene, reported by Kochi et al, 40 or by Na/Hg. 22 Kochi et al also found that the formed [Fe 3 (CO) 9 (PR) 2 ] − species with two equivalent a( 31 P) constants slowly (within hours) converted to another type of a radical anion with a gfactor near 2.04 and nonequivalent a( 31 P) constants of 25 and 3 G. The authors suggested that the second type of species results from a μ 3 -to μ 2 -binding transition of one of the Fe−P bonds, causing a loss of equivalence between both P atoms.…”
Section: ■ Results and Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The EPR signal is a triplet with a 1:2:1 intensity ratio ascribed to two equivalent 31 P nuclei with a( 31 P) of 13.3 G. The time/potential profile of the EPR intensity allows its assignment to the first reduction step. The EPR parameters of the radical anion are very similar to those of a series of [Fe 3 (CO) 9 (PR) 2 ] − radical anions produced by chemical reduction of the corresponding Fe 3 (CO) 9 (PR) 2 clusters by cobaltocene, reported by Kochi et al, 40 or by Na/Hg. 22 Kochi et al also found that the formed [Fe 3 (CO) 9 (PR) 2 ] − species with two equivalent a( 31 P) constants slowly (within hours) converted to another type of a radical anion with a gfactor near 2.04 and nonequivalent a( 31 P) constants of 25 and 3 G. The authors suggested that the second type of species results from a μ 3 -to μ 2 -binding transition of one of the Fe−P bonds, causing a loss of equivalence between both P atoms.…”
Section: ■ Results and Discussionsupporting
confidence: 78%
“…This in turn supports absence of a communication through the core and the presence of a noncoupled class I system according to Robin and Day . That oxidation of ferrocenyl substituents can affect IR bands of adjacent carbonyl ligands could be shown for 1,1′-dithiolatoferrocene-hexacarbonyldiiron . Further increase of the potential results in the formation of [ 4 ] 2+ , accompanied by an equal hypsochromic shift of ∼10 cm –1 for the most intense bands.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The ferrocenyl core in both type of compounds provides unique geometric properties that cannot be achieved by condensed aromatics (Figure 1, Figure S1, Figure S2) [19,20] . Additionally, the conformational flexibility around the Cp−Fe bond of the 1,1’‐substituted sandwich allows for the synthesis of di‐ [5,7,21,22] and polymeric complexes [23] and the bending of the backbone for unique connectivity modes [24] . The 1,2‐substitution pattern (Figure 1) exhibits an increased P⋅⋅⋅P distance and a wider opening angle compared to 1,2 phenylenes, whereby a ferrocenyl annelation still occurs.…”
Section: Introductionmentioning
confidence: 99%